Hubungan Pengetahuan, Sikap dan Ketersediaan Sarana dengan Pengelolaan Sampah Penghuni Kost di Dusun 1, Desa Penfui Timur - Maria Frasiska Lose Labamaking; Soni Doke; Cathrin Wea Djogo Geghi; Marylin Susanti Junias (Yayasan Literasi Sains Indonesia, 2025)
Waste is one of the environmental health problems that remains a major challenge in various regions. Population growth and changes in consumption patterns have led to increasing waste volumes, while suboptimal waste management has led to environmental pollution, aesthetic disturbances, and the risk of environmental-based diseases such as diarrhea, dengue fever, and skin infections. This waste problem becomes increasingly important when associated with the lifestyle of boarding house residents who generally have limited space, facilities, and time to carry out optimal waste management. This study aims to analyze the relationship between knowledge, attitudes, and availability of facilities with waste management of boarding house residents. The study was conducted in Hamlet 1, Penfui Timur Village, Kupang Tengah District, Kupang Regency and was carried out on May 12-June 12, 2025. The research design used in this study was an analytical survey with a cross-sectional study design approach. The study population was boarding house residents in Hamlet 1, Penfui Timur Village with a total sample of 100 people. The collected data were analyzed using the chi-square test. The results of the bivariate analysis showed that there was no relationship between knowledge and waste management (p-value = 0.687), there was a relationship between attitudes and waste management (p-value = 0.046), and there was also no relationship between the availability of infrastructure and waste management (p-value = 0.345) of boarding house residents.